Evaluation of Existing Drainage Capacity for Flood Mitigation Measures at Segamat, Malaysia - Mohd Yusoff, Mohd Azlan (International Journal of Integrated Engineering, 2019)
The drainage system is used for controlling, management, or convey the storm water into certain areas. The system is used to prevent the entry of water into the soil structure and reduce the strength and durability of the ground. The present study aimed to evaluate the existing drainage capacity and propose a conceptual flood mitigation measures. The study area was located at Kampung Paya Lang, Segamat with two types of drainage system included concrete and earth drainage. Determintion of the rainfall hydrograph was investigated in the site area, survey of existing drainage (cross-section), drainage profile and flow measurement in each existing drainage. The data of rainfall was analyzed in XP SWMM software to know the storm water movement when the existing drainage is not properly well. The rainfall data were obtained from Department of Irrigation and Drainage (DID) in the form of hours and minutes for nearby rain station for a period of 10 years from 2006 to latest. Therefore, the inventory for each drainage should fulfill the requirement of MSMA. The results revealed that the existing drainage was less effective in the process to convey the flow of storm water runoff due to the continuous rain occur that would cause overflow of drainage and flooding. The existing concrete drainage and earth drain was less effective to prevent the occurrence of flooding situation in every catchment area at the study area location.